1990
DOI: 10.1002/app.1990.070400710
|View full text |Cite
|
Sign up to set email alerts
|

Multiple transitions in a dimethacrylate network

Abstract: SynopsisTriethylene glycol dimethacrylate, TEGDM, was cured to various dose levels (0.15-2.0 Mrad) by y-irradiation at 4OoC and its dynamic mechanical properties were evaluated. The resultant products had up to four transition phenomena dependent upon dose. The highest temperature transition (IV) was due to the ultimate glass transition. Transition I11 (ca. 40'C) was due to additional reaction occurring just above the cure temperature. Transition I (ca. -60°C) occurred at low doses and was associated with resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…As can be seen in Figure , for no sample can a secondary mechanical relaxation be noticed, and the principal relaxation is always broad, which highlights the presence of many heterogeneities at the nanometer scale in the network and confirms the XRD results . The characteristics of the mechanical relaxations are summarized in Table .…”
Section: Resultssupporting
confidence: 73%
“…As can be seen in Figure , for no sample can a secondary mechanical relaxation be noticed, and the principal relaxation is always broad, which highlights the presence of many heterogeneities at the nanometer scale in the network and confirms the XRD results . The characteristics of the mechanical relaxations are summarized in Table .…”
Section: Resultssupporting
confidence: 73%
“…While these network polymers have very desirable properties, the network structure formed by photopolymerizing multifunctional monomers is extremely heterogeneous. , It has been of significant interest to characterize this structural heterogeneity by using various experimental techniques as well as to develop a theoretical understanding of these heterogeneities. It has been noted in the literature 9-11 that both very highly cross-linked polymer-rich regions, known as microgels, and “pools of unreacted monomer” are found in the same network. Such a range of environments is reflected in the mechanical response of the materials as wide glass transition regions. ,, Therefore, by examining the glass transitions and the distribution of relaxation times, the distribution of mobilities (or microenvironments) can be characterized. In our earlier work, dynamic mechanical analyses (DMA) performed on photopolymerized cross-linked polymers have been described.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Also, termination rate decreases significantly and reduces end conversion to lower values, due to trapped inactive radicals 21 and higher glass transition temperature (T g ), for cross-linked PMMA compared to linear PMMA. 17,22,23 The presence of a solvent leads to the same results, namely delay and reduction of the Trommsdorff effect and increase of the end-conversion ratio, for linear and for cross-linked PMMA. 17,19 The mechanism generally admitted 19,24 consists of the formation of microgels at the early stage of the cross-linking copolymerization.…”
Section: Introductionmentioning
confidence: 63%
“…There are very few kinetic studies related to free-radical cross-linking copolymerization of MMA with low concentration of multifunctional vinyl monomers. However, it has been shown that an increase in the concentration of cross-linker induces higher polymerization rates ,, and autoacceleration (Trommsdorff effect) at lower conversion ratios. , Also, termination rate decreases significantly and reduces end conversion to lower values, due to trapped inactive radicals and higher glass transition temperature ( T g ), for cross-linked PMMA compared to linear PMMA. ,, The presence of a solvent leads to the same results, namely delay and reduction of the Trommsdorff effect and increase of the end-conversion ratio, for linear and for cross-linked PMMA. , The mechanism generally admitted , consists of the formation of microgels at the early stage of the cross-linking copolymerization. As the reaction proceeds, the concentration of these microgels increases up to agglomeration and gelation of the reactive medium.…”
Section: Introductionmentioning
confidence: 99%